Bina Vokalia Learning As Extracurricular Activities In The Integrated Early Chilhood Education (PAUD) Of Salatiga Children Center (Jurnal Seni Musik, 2020)
The process of learning in early childhood education and kindergarten is never apart from musical activities, although it is mostly just singing and dancing. Singing is one of the learning activities that is carried out daily from beginning of class to the end of class. Integrated PAUD Satya Wacana Children Center Salatiga provides a form of extracurricular Bina Vokalia at school to support learning, improve and develop student talent in singing. Vocal teaching of children is definitely different than adults, the delivery of the song material should be interesting to learners and in teaching the child's vocal techniques is need patience and technique. In view of today's modern times, many parents are increasingly giving their children activities outside school, especially music. Integrated PAUD Satya Wacana Children Center provides a vocal building learning facility that might develop a child's talent for music. The problem considered in the study is "how the learning process of Bina Vokalia and how the obstacles and solutions to delivering vocal materials in integrated PAUD Satya Wacana Children Center " The study employs qualitative research methods with descriptive exposure. Research subjects are students and teachers of integrated PAUD Satya Wacana Children Center salatiga. Data collection results with observation techniques, interviews, documentation and data analysis. Data analysis techniques divide into three phases that are data reduction, data presentation, and conclusions. The results of the interviews and observations already collected include the documentation, pictures, photographs, field notes, personal notes, and other documents after studied and researched than reduced to an abstraction. As the results of research, researchers concluded that the Bina Vokalia PAUD activities could help students develop singing skills early on, not only good vocal techniques but training children to be bolder and more confident in the activities organized by the foundation. The advice is that music teachers should not be absent too often, requiring an additional event of school in order to make children more active and creative. It is necessary to increase the practice time and musical facilities so the children do not become bored prematurely.